E-Waste Management Trend in Ethiopia: Strategies for Extending Electronics Lifecycles - Hirpa, Hawi K.; Desissa, Temesgen D.; Duflou, Joost R. (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The rapid e-waste generation poses a significant environmental challenge, necessitating sustainable approaches to managing electronic product lifecycles. This paper investigates how repair practices in Ethiopia affect the lifespan of electronic devices. It has been observed that, compared to several reference countries, electronics in Ethiopia tend to have slightly longer lifespans, primarily due to extensive repair and reuse practices. In this study, we conducted a lifespan analysis by collecting lifespan data from various maintenance shops. The Weibull distribution method was used to analyze the lifespan of different categories of devices. The data revealed that the average lifespans of LCD TVs, LCD monitors, laptops, and smartphones are 12.0, 11.0, 10.7, and 6.4 years, respectively. The findings highlight the significant role of repair and refurbishment in extending device longevity while also revealing a growing trend in e-waste generation. This study explores the impact of repair practices on extending electronic device lifespans in Ethiopia, considering policy approaches that support repair and reuse. It also shows the need for collaboration among repair practitioners, policymakers, and consumers to strengthen sustainable e-waste management efforts. This research aims to contribute to environmental preservation and sustainable development in the country by fostering a circular economy.